PULP Guide: Finding legal information in South Africa - Third edition - Edited by Shirley Ann Gilmore (Pretoria University Law Press (PULP), 2014)
PULP Guide: Finding legal information in South Africa - Third edition Edited by Shirley Ann Gilmore 2014 ISBN: 978-1-920538-28-6 Pages: 115 Print version: Available Electronic version: Free PDF available